Environmental sources of Cryptococcus neoformans species complex in Kampala, Uganda: A preliminary study - Beatrice Achan; Abel Wembabazi; Tonny Luggya; Innocent Robert Ebwongu; Benson Musinguzi; Herbert Itabangi; Henry Kajumbula; David Meya (PLoS ONE, 2025)
Objectives We aimed to determine the environmental sources of C. neoformans and C. gattii species complexes in Uganda. Methods One hundred fifty (n = 150) environmental specimens of chicken droppings, marabou stork bird droppings and eucalyptus tree barks in Uganda were examined phenotypically. The specimens were grown on Sabouraud dextrose agar and the colonies examined by India ink microscopy, urea hydrolysis and formation of blue colonies on chromogenic L-Canavanine glycine blue bromothymol blue agar of C. gattii species complex Results The prevalence of C. neoformans species complex was 4% (6/150). Of the positive environmental samples from which C. neoformans species complex were isolated; the predominant source was marabou stork droppings; 8% (2/25) followed by eucalyptus tree barks; 3.96% (4/101). However, there was no Cryptococcus gattii species complex; 0% (0/150). Conclusion In Uganda, the environmental sources of C. neoformans species complex are marabou stork droppings and eucalyptus tree barks, however, there seems to be no Cryptococcus gattii species complex.